Psychosis: a rare but serious psychiatric anomaly in patients with sarcoidosis - Kapoor, Shailendra (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
I read with great interest the recent article by Hinz et al. 1 Interestingly, sarcoidosis may rarely be associated with manic or psychotic symptoms. Psychotic disorders are seen in 6.3% of all patients with sarcoidosis, especially in patients with “neurosarcoidosis”. 2 Neurosarcoidosis usually occurs in conjunction with systemic sarcoidosis. Rarely, neurosarcoidosis may be present as an isolated syndrome with no systemic involvement. Overall psychosis is seen in 16.9% of patients with neurosarcoidosis. 3 The cerebrum and the meninges are the sites most commonly involved. However, the hypothalmus may also be involved in some patients. Involvement of the “nucleus accumbens” has also been reported, resulting in altered dopaminergic transmission and subsequent psychosis. 4